The effects of social media addiction on college students’ psychological anxiety: the mediating role of self-efficacy and coping styles - Chen, Jing; Yu, Zihan; Yu, Zekai; Ni, Ruiyang; Zhou, Jiayao; Qu, Jiahao (Frontiers in Psychology, 2025)
BackgroundSocial media addiction (SMA) has emerged as a significant mental health concern among Chinese college students, particularly within the context of intense academic competition and collectivist cultural pressures. While the direct relationship between SMA and psychological anxiety is well-documented, the underlying psychological mechanisms remain poorly understood.ObjectiveThis study investigated the complex pathways through which social media addiction influences psychological anxiety among Chinese college students, with particular focus on the mediating roles of self-efficacy and coping styles within China’s unique cultural and educational context.MethodsUsing stratified random sampling, 615 valid responses were collected from Chinese college students across different university types and geographic regions (response rate: 92.86%). Structural equation modeling (SEM) was employed to examine the relationships between SMA, self-efficacy, coping styles (positive and negative), and psychological anxiety. The quantitative analysis was supplemented with semi-structured interviews of 25 participants to provide contextual insights into the identified mechanisms.ResultsThe study found that social media anxiety (SMA) directly increases anxiety (β = 0.78, p < 0.001) and has indirect effects through reducing self-efficacy (β = −0.73, p < 0.001), which accounts for 23% of the total effect, and promoting negative coping strategies while undermining positive ones, contributing 20.32%. A chain mediation pathway where SMA reduces self-efficacy, affecting coping strategies, amplifies anxiety by 17%. Qualitatively, 72% reported social comparison-induced self-worth erosion, and 68% engaged in “doomscrolling,” creating anxiety cycles.ConclusionThis study provides robust evidence for a multi-pathway model linking social media addiction to psychological anxiety among Chinese college students. SMA’s effects go beyond direct impacts, disrupting key psychological defenses like self-efficacy and adaptive coping. The chain mediation effect exposes a concerning sequential psychological erosion, especially given the sample’s high baseline anxiety (mean SAS = 63.08). These findings emphasize the need for holistic interventions targeting addiction, boosting self-efficacy, and fostering adaptive coping. They also highlight the importance of university mental health services and digital wellness programs in tackling the escalating mental health challenges faced by digitally immersed students.